Antiretroviral therapy and Kaposi's sarcoma trends and outcomes among adults with HIV in Latin America. Issue 1 (6th January 2021) - Castilho, Jessica L; Kim, Ahra; Jenkins, Cathy A; Grinsztejn, Beatriz; Gotuzzo, Eduardo; Fink, Valeria; Padgett, Denis; Belaunzaran‐Zamudio, Pablo F; Crabtree‐Ramírez, Brenda; Escuder, Maria Mercedes; Souza, Rosa Alencar; Tenore, Simone B; et al.
Abstract: Introduction: Kaposi's sarcoma (KS) remains the most frequent malignancy in persons living with HIV (PWH) in Latin America. We examined KS trends and outcomes from Latin American clinical sites in the era of increased access to antiretroviral therapy (ART). Methods: Cohorts in Brazil, Peru, Mexico, Honduras, Argentina and Chile contributed clinical data of PWH ≥16 years old from 2000 to 2017, excluding patients with KS diagnosed before clinic enrolment. We compared KS incidence over time using multivariable incidence rate ratios. Predictors of KS before/at or after ART initiation and of mortality after KS were examined using Cox regression. Results: Of 25 981 PWH, 481 had incident KS, including 200 ART‐naïve and 281 ART‐treated patients. From 2000 to 2017, the incidence of KS decreased from 55.1 to 3.0 per 1000 person‐years. In models adjusting for CD4 and other factors, the relative risk for KS decreased from 2000 to 2008. Since 2010, the adjusted risk of KS increased in the periods before and ≤90 days after ART initiation but decreased >90 days after ART. In addition to low CD4 and male‐to‐male sex, KS risk after ART was associated with age and history of other AIDS‐defining illnesses. Mortality after KS (approximately 25% after five years) was not associated with either year of KS diagnosis nor timing of diagnosis relative to ART initiation. Conclusions: KS incidence in Latin America has remained stable in recent years and risk is highest before and shortly after ART initiation. Early diagnosis of HIV and ART initiation remain critical priorities in the region.